Crystal structures of bis[2-(pyridin-2-yl)phenyl-κ2N,C1]rhodium(III) complexes containing an acetonitrile or monodentate thyminate(1−) ligand - Mika Sakate; Haruka Hosoda; Takayoshi Suzuki (Acta Crystallographica Section E: Crystallographic Communications, 2016)
The crystal structures of bis[2-(pyridin-2-yl)phenyl]rhodium(III) complexes with the metal in an octahedral coordination containing chloride and acetonitrile ligands, namely (OC-6-42)-acetonitrilechloridobis[2-(pyridin-2-yl)phenyl-κ2N,C1]rhodium(III), [RhCl(C11H8N)2(CH3CN)] (1), thyminate(1−) and methanol, namely (OC-6-42)-methanol(5-methyl-2,4-dioxo-1,2,3,4-tetrahydropyrimidin-1-ido-κN1)bis[2-(pyridin-2-yl)phenyl-κ2N,C1]rhodium(III), [Rh(C11H8N)2(C5H5N2O2)(CH3OH)]·CH3OH·0.5H2O (2), and thyminate(1−) and ethanol, namely (OC-6-42)-ethanol(5-methyl-2,4-dioxo-1,2,3,4-tetrahydropyrimidin-1-ido-κN1)bis[2-(pyridin-2-yl)phenyl-κ2N,C1]rhodium(III), [Rh(C11H8N)2(C5H5N2O2)(C2H5OH)]·C2H5OH (3), are reported. The acetonitrile complex, 1, is isostructural with the IrIII analog. In complexes 2 and 3, the monodeprotonated thyminate (Hthym−) ligand coordinates to the RhIII atom through the N atom, and the resulting Rh—N(Hthym) bond lengths are relatively long [2.261 (2) and 2.252 (2) Å for 2 and 3, respectively] as compared to the Rh—N bonds in the related thyminate complexes. In each of the crystals of 2 and 3, the complexes are linked via a pair of intermolecular N—H...O hydrogen bonds between neighbouring Hthym− ligands, forming an inversion dimer. A strong intramolecular O—H...O hydrogen bond between the thyminate(1−) and alcohol ligands in mutually cis positions to each other is also observed.